Antifungal Activity Against Phytophthora capsici leon Which Causes Root Neck Burn in Pepper Around Kahramanmaras - EREN KIRAN*, ÖZLEM; ILÇIM, AHMET; DIGRAK, METIN (Asian Journal of Chemistry, 2024)
In the present study effects of essential oil and extracts obtainedfrom plants on Phytophthora capsici leon which is a pathogen fungus forpepper plants (Capsicum annuum L.) have been investigated. Essentialoils and chloroform, methanol and hexane extracts of various plantsincluding Pistachia terebinthus L., Quercus infectoria Oliv., Pinus brutiaTEN., Juniperus oxycedrus L., Cedrus libani A.Rich., Pinus nigra L.,Abies cilicica Carr., Salvia aucheri L., Phlomis bourgei Boiss., Parmeliafurfuracea L., Crocus chrysanthus (Herb.) Herb., Rumex scutatus L.,Myrtus communis L., Eugenia caryophyllata Thumb., Smyrniumolusatrum L., Ajuga orientalis L., Astragalus schizopterus Boiss., Papaverhybridum L. Salvia multicaulis Vahl., Salvia viridis L., Satureja cilicicaP.H., Satureja hortensis L., have been used. It has been found that essentialoils and extracts of some plants have repressive effect on growth ofPhytophthora capsici.